Measurement of b-jet shapes in inclusive jet production in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2008)
We present a measurement of the shapes of b-jets using 300pb-1 of data obtained with the upgraded Collider Detector at Fermilab (CDF II) in pp̄ collisions at center-of-mass energy s=1.96TeV. This measurement covers a wide transverse momentum range, from 52 to 300GeV/c. Samples of heavy-flavor enhanced jets together with inclusive jets are used to extract the average shapes of b-jets. The b-jets are expected to be broader than inclusive jets. Moreover, b-jets containing a single b-quark are expected to be narrower than those containing a bb̄ pair from gluon splitting. The measured b-jet shapes are found to be significantly broader than expected from the pythia and herwig Monte Carlo simulations. This effect may arise from an underestimation of the fraction of b-jets originating from gluon splitting in these simulations. The jet shape distributions provided in this paper could be compared to any full Monte Carlo simulation and could be used to further constrain the various parameters. © 2008 The American Physical Society.